Bike sharing differences among Millennials, Gen Xers, and Baby Boomers: Lessons learnt from New York City's bike share. (October 2018) - Wang, Kailai; Akar, Gulsah; Chen, Yu-Jen
Highlights: Varying effects of weather and built environment on bike sharing usage are examined. The focus is cohort differences among Millennials, Gen Xers and Baby Boomers. We estimate zero-inflated negative binominal models for bike-share trip productions. NYC's Citi Bike data are used to estimate trip productions at bike-share stations. Results reveal varying effects of hypothesized variables on different age cohorts. Abstract: There is a growing literature on the changing travel patterns in the United States. The changes are largely driven by the emerging shared-mobility services and the travel behavior of the younger generations. This study builds on an investigation of Millennials', Gen Xers' and Baby Boomers' bike sharing ridership in New York City. This study examines station-level bike share use focusing on whether and how the effects of land-use and built environment vary across different population segments. Using New York's Citi Bike system data, we develop zero-inflated negative binominal models to estimate hourly trip productions at stations for five age cohorts: younger Millennials (born 1995 to 2000), mid Millennials (1989 to 1994), older Millennials (born 1979 to 1988), Generation Xers (born 1965 to 1978), and Baby Boomers (born 1946 to 1964). Consistent with the literature, our results suggest that weather related variables, land-use and built environment characteristics have significant effects on the overall bike sharing usage. Our findings also reveal variations across age cohorts. For example, intersection density is positively related to younger Millennials' bike share trip production. However, this factor is not statistically significant for other age groups. Our findings provide valuable insights for planners and policy-makers, and set the basis for improving the understanding of cohort differences in bike sharing demand.